Time-Dependent Analysis of Plasmalogens in the Hippocampus of an Alzheimer’s Disease Mouse Model: A Role of Ethanolamine Plasmalogen - Abul Kalam Azad; Abdullah Md. Sheikh; Md. Ahsanul Haque; Harumi Osago; Hiromichi Sakai; Abu Zaffar Shibly; Shozo Yano; Makoto Michikawa; Shahdat Hossain; Shatera Tabassum; Garu A.; Xiaojing Zhou; et al. (Brain Sciences, 2021)
Plasmalogens are alkenyl-acyl glycerophospholipids and decreased in post-mortem Alzheimer’s disease (AD) brains. The aim of this study is to investigate the time-dependent changes of plasmalogens in the hippocampus of an AD model mouse (J20). Plasmalogen levels at 3, 6, 9, 12 and 15 months were analyzed by liquid-chromatography-targeted-multiplexed-selected-reaction-monitoring-tandem-mass-spectrometry (LC-SRM/MS). Reactive oxygen species (ROS) levels were evaluated using dichlorofluorescein diacetate (DCF-DA). Plasmalogen synthesizing enzyme glycerone-phosphate O-acyltransferase (GNPAT) and late endosome marker Rab7 levels were quantified by Western blotting. GNPAT localization, changes of neuronal and glial cell numbers were evaluated by immunostaining. Compared to wild-type mice (WT), total plasmalogen-ethanolamine, but not plasmalogen-choline levels, were increased at 9 months and subsequently decreased at 15 months in J20 mice. A principal component analysis of plasmalogen-ethanolamine species could separate WT and J20 mice both at 9 and 15 months. Both GNPAT and Rab7 protein were increased in J20 mice at 9 months, whereas GNPAT was decreased at 15 months. ROS levels were increased in J20 mice except for 9 months. Our results suggest that increased plasmalogen-ethanolamine could counteract ROS levels and contribute to the phagocytosis process in J20 mice at 9 months. Such results might indicate a transient protective response of plasmalogen-ethanolamine in AD conditions.